2022
DOI: 10.52916/jmrs224074
|View full text |Cite
|
Sign up to set email alerts
|

Acute Ischemic Stroke in a Young Woman with an Otherwise Asymptomatic SARS-CoV-2 Infection

Abstract: It was well-observed that SARS-CoV-2 may cause a hypercoagulable state in hospitalized patients. Often these hospitalized patients exhibit severe upper respiratory symptoms with hypoxia, requiring high amounts of oxygen support. In this study, we report a young healthy 30-year-old woman with no medical problems, who experienced an embolic stroke due to an otherwise asymptomatic SARS-CoV-2 infection in July 2020. The patient presented to the emergency department after experiencing sudden slurred speech, dizzin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…In addition, within the past 2 years, we have seen acute ischemic stroke as a complication of patients with severe SARS-CoV-2 infection due to its precipitation of a hypercoagulable state [ 34 ]. There has even been a reported case of stroke in a young healthy woman with an asymptomatic SARS-CoV-2 infection as well [ 35 ]. Studies have shown that in-hospital treatment with heparin was associated with lower mortality in severe COVID-19 patients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, within the past 2 years, we have seen acute ischemic stroke as a complication of patients with severe SARS-CoV-2 infection due to its precipitation of a hypercoagulable state [ 34 ]. There has even been a reported case of stroke in a young healthy woman with an asymptomatic SARS-CoV-2 infection as well [ 35 ]. Studies have shown that in-hospital treatment with heparin was associated with lower mortality in severe COVID-19 patients [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…While it is a disease that mainly involves the lungs, multiple organs, including neurological symptoms, have been described frequently [ 3 ]. Even young adults with seemingly asymptomatic COVID-19 infections can end up suffering a thrombotic stroke that adversely affects their health [ 4 ]. Currently, there is no definitive antiviral agent to treat hospitalized patients with severe COVID-19 [ 5 ].…”
Section: Introductionmentioning
confidence: 99%